Alumina‐Supported Alpha‐Iron(III) Oxyhydroxide as a Recyclable Solid Catalyst for CO2 Photoreduction under Visible Light. Issue 26 (12th May 2022) - An, Daehyeon; Nishioka, Shunta; Yasuda, Shuhei; Kanazawa, Tomoki; Kamakura, Yoshinobu; Yokoi, Toshiyuki; Nozawa, Shunsuke; Maeda, Kazuhiko
Abstract: Photocatalytic conversion of CO2 into transportable fuels such as formic acid (HCOOH) under sunlight is an attractive solution to the shortage of energy and carbon resources as well as to the increase in Earth's atmospheric CO2 concentration. The use of abundant elements as the components of a photocatalytic CO2 reduction system is important, and a solid catalyst that is active, recyclable, nontoxic, and inexpensive is strongly demanded. Here, we show that a widespread soil mineral, alpha‐iron(III) oxyhydroxide (α‐FeOOH; goethite), loaded onto an Al2 O3 support, functions as a recyclable catalyst for a photocatalytic CO2 reduction system under visible light ( λ >400 nm) in the presence of a Ru II photosensitizer and an electron donor. This system gave HCOOH as the main product with 80–90 % selectivity and an apparent quantum yield of 4.3 % at 460 nm, as confirmed by isotope tracer experiments with 13 CO2 . The present work shows that the use of a proper support material is another method of catalyst activation toward the selective reduction of CO2 . Abstract : A widespread soil mineral, alpha‐iron(III) oxyhydroxide, which is loaded onto an alumina support, works as a recyclable catalyst for CO2 reduction. In the presence of a Ru II photosensitizer, the catalyst produces formic acid with 80–90 % selectivity and an apparent quantum yield of 4.3 % at 460 nm.